ESTIMATE VALUE OF HEALTH INSURANCE PREMIUM THROUGH BAYESIAN METHOD - SETIA BAKTI , SEVAN
Health is important in life. One of the efforts in maintaining health from various conditions is to insure themselves to health insurance companies. For that, need a proper calculation in determining the premium value in order to avoid damage in the next period. The Bayesian method is one good method of determining the premium value because the parameter which estimated, considered a random variable with a distribution called prior distribution. In this Final Project, what will be discussed is the selection of models that can model the values of health insurance claims and use the model to predict the value of claims in the next period. Estimation of parameter uses Markov Chain Monte Carlo (MCMC) algorithm as a numerical solution in complex posterior distribution problems. Data are Processed from health insurance claims data of 2015 for ages 24 to 28 years and will predict the value of claim for the next period.